Peran Pasraman dalam Mewujudkan Kehidupan Masyarakat yang Harmonis - I Wayan Sudika (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
Human life between physical needs (clothing, shelter and health) and spiritual needs such as the need for compassion, security, self-esteem, sense of freedom, sense of success and curiosity. Therefore, the burden of happiness can not be done only for the environment, but also must be built by health personnel or their inner self. Development in the field of education in addition to education in the family and formal education, can be done through pasramanpasraman existing in the community including those in the village pakraman.Keywords: Spiritual Development, Ethics, and Local Wisdom.